Age, Work Experience, and Tenure as Determinants of Pharmacists’ Provision of Self‑Medication Information - Aryani, Fina; Delphiarnis, Syahvira; Muharni, Septi; Dewi, Ratna Sari; Humairah, Anugrah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Self-medication refers to the practice by which individuals use medicines obtained without a physician’s prescription to treat their symptoms or pain. However, errors in medication use remain common in self-medication practices; therefore, pharmacists play an important role in providing drug information. This study aimed to analyze the factors influencing the provision of drug information for self-medication by pharmacists. A cross-sectional study was conducted involving 100 pharmacists in Pekanbaru, Indonesia. Data were collected through participant observation and analyzed using t-tests and ANOVA. The analysis showed that the p-values for each candidate determinant were as follows: gender = 0.287, work experience = 0.014, secondary employment = 0.222, age = 0.022, education = 0.191, weekly working hours = 0.000, and daily working hours = 0.000. It can therefore be concluded that the determinants of pharmacists’ provision of drug information in self-medication are age, work experience, and working hours.Keywords: pharmacist; drug information provision; self-medication